Zinovii Ostapovych Melnyk (1935-1983) - M.M. Bokalo; O.M. Buhrii; V.M. Kyrylych; O.Z. Slyusarchuk (Математичні Студії)
The life and creative path of the outstanding scientist and Dean of the Faculty of Mechanics and Mathematics of Lviv University Z. O. Melnyk is considered